Employee Involvement (EI) and Workforce Agility (WA): The Mediating Role of Psychological Empowerment (PE) - Johannes Aldrin Timbuleng; Bernhard Tewal; Victor P. K. Lengkong; Irvan Trang; Greis M. Sendow (Universitas Syiah Kuala, 2023)
Objective –This study has two goals: to investigate the impact of employee participation on WA, and to analyse how PE affects EI and WA at Universitas Katolik De La Salle Manado.Methodology –The sample consists of 110 lecturers from Universitas Katolik De La Salle Manado, with the study using EI, WA, and PE as the main variables for generating hypotheses to be tested via moderating regression analysis.Results –This study's results demonstrate that EI positively influences WA and is moderated by PE at Universitas Katolik De La Salle Manado.Research limitations/implications –This study suggests that Indonesian higher education institutions should prioritize EI and PA practices. This can be achieved through decision-making opportunities, training programs, autonomy, and employee recognition. The interaction between these factors does not significantly explain WA variance. Organizations should focus on individual implementations to maximize their impact. Further research is needed to explore other moderating variables and alternative models.Novelty/Originality –The study examines the relationship between EI, PE, and WA in Indonesian higher education institutions, expanding on previous research on these dimensions.